KINERJA KEUANGAN PADA HOTEL MILIK XYZ DENGAN PENGGUNAAN OPERATOR HOTEL: FINANCIAL PERFORMANCE IN XYZ HOTELS USING HOTEL OPERATORS - Miranti Miranti; Noer Azam Achsani; Bayu Bandono (School of Business, Bogor Agricultural University (SB-IPB), 2020)
The purpose of this study is to analyze the financial performance of XYZ’s hotels by using hotel operators. XYZ’s hotels for the last nine years have been managed by AHH to increase the productivity of hotel performance. Historical financial performance show that the three XYZ hotels did not achieve the target over the last five years. Meanwhile, until August 2019 XYZ’s hotels showed a decrease in income above 5% and net profit after tax above 40%. To analyze hotel financial performance used financial ratios, company value added (EVA), and dividend payout ratio. Next to analyze the differences in the financial performance of XYZ hotels between before and after managed by hotel operators used the t-independent test method. The results of the analysis of financial performance show that MHH and SPH had good hotel financial performance during the study period, while BIH showed a declined trend in financial performance with negative EVA. The results of the t-independent test research showed that AHH as a hotel operator failed to improve the hotel's financial performance and did not provide added value to the three hotels owned by XYZ. Keywords: financial performance, economic value added, dividend payout ratio, hotel management, hospitality industry